TAFSIR INDONESIA (Studi Kritis atas Tafsir Basmalah karya Kyai Asmuni) - Ansor Bahary; Komaruddin Fitroni (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2022)
When the mufasir interprets Bismillāh al-Raḥmān al-Raḥīm into a work of interpretation, the understanding and meaning produced is generally based on prayer and the relation of fā‘idah isti’ānah (asking for help like a servant to His Lord) usually other interpretations. This output is caused by the fact that basmalah is interpreted in its entirety, without specifying the interpretation of the sentences in it, or it may be detailed but not upproached with grammatical-arabic discourse. Slightly different from the interpretation carried out by Kyai Asmuni, it does not only focus on this but raises at least three scientific domains such as theology (al-’aqīdah), fiqh (al-h}ukm), and sufism (al-akhlāq). Even at the same time, this realm can also became an icon of its interpretation style and at the same time demarcate it from other interpretaions. Understanding and meaning of this religious trilogy was originally explored by the author through his meditation on the basics and bases such as writing lafal (kitābah), reading (qira‘at), language (lughah), syintax (nahwu), literature (balāghah), and logic (mantiq) in the context of reading “ba”, “ism”, jalalah “Allah” and “al-Rahman al-Rahim”. This basics and bases instrument is certainly the initial tool for exploration where analytical mapping is the main approach and the elaborative tools presented reveal various methods (manhaj) and the style (laun) of its interpretation. The natur of the data, which is library research, inspires the choice of research in the qualitative type. The descriptive-argumentative data explanation is read and design through inductive analysis (inductive observation)